Akad Wakâlah dan Samsarah sebagai Solusi atas Klaim Keharaman Dropship dalam Jual Beli Online - Ika Yunia Fauzia (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2015)
Online business (selling-buying) has become prominent in the past few years ago as demand increases. This kind of business forms a positive effect of the development of internet which produces new business-men. Along with the development of online business, there emerges dropship system which is mostly undertaken by female entrepreneurs. Despite its negative effect, dropship system has positive influence, i.e. creating positive activities for women and therefore empowering them. The polemics of dropship is still going on. According to some Muslim jurists, dropship is forbidden (ḥarâm) because the practicioners of this system sell items only from picture. Moreover, the items sold have not been the property of the practicioners. This article deals with the benefit of wak?lah and samsarah contract used to accommodate the dropship system. The specification of both contracts is explained in detail in order for this system to be undertaken as wakalah and samsarah contract. The practicioners of dropship as wâkil, and suppliers as muwakkil, or the practicioners of dropship as simsâr with some conditions that should be accorded to the contract in the beginning of transaction.